Seasonal variability changes and trends in minimum discharge for Western Balkan rivers - Igor Leščešen; Slobodan Gnjato; Duško Vujačić; Ana M. Petrović; Ivan Radevski (Journal of Hydrology: Regional Studies, 2025)
Study region: This study focuses on the Western Balkans, specifically analyzing river basins across Bosnia and Herzegovina, Serbia, Montenegro, and North Macedonia. Study focus: The objective is to investigate long-term trends in minimum river discharges from 1961 to 2020, with an emphasis on low-flow events and their seasonal dynamics. Minimum discharge magnitudes were categorized as M1 (lower) and M2 (higher) based on the 1961–1990 baseline period. Seasonal Mann–Kendall trend tests were applied to detect significant changes in low-flow frequency and intensity across a representative network of gauging stations. New hydrological insights for the region: The results reveal a statistically significant increase in the frequency of M1 low-flow events during summer, indicating more severe low-flow conditions. This trend is especially prominent across central and southern stations. Winter season analyses also suggest rising minimum discharge values, albeit with spatial variability. Conversely, M2 events, indicative of relatively higher minimum flows, show a consistent and statistically significant decline across nearly all stations during summer. These opposing trends reflect a regional intensification of summer low-flow conditions and a possible shift in the seasonal flow regime. The findings underscore the growing vulnerability of Western Balkan river systems to hydrological droughts, likely driven by climate change and local watershed pressures. These insights hold practical relevance for water resource management, highlighting the urgency of adaptive strategies for drought mitigation and ecological flow preservation.